2009
DOI: 10.1148/rg.295085183
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution MR Imaging of the Cervical Arterial Wall: What the Radiologist Needs to Know

Abstract: The emergence of high-resolution rapid imaging methods has enabled magnetic resonance (MR) imagers to noninvasively image the fine internal structure of cervical arterial walls. In this article, a comprehensive guide to performing high-resolution MR imaging of cervical arteries is provided, including the choice of coils, sequences, and imaging parameters, as well as tips for optimal image quality. Explanations and illustrations are given of using high-resolution MR imaging to quantify plaque volume, determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 48 publications
4
53
0
Order By: Relevance
“…Theoretically, the ideal VW imaging protocol would include images of all three image contrast weightings and a T1-weighted sequence after contrast agent administration to assess intracranial VW disease in the same fashion as has been done for years for their extracranial counterparts (46). However, no clear evidence yet exists on the clinical relevance of multicontrast MR imaging protocols for intracranial VW disease.…”
Section: How I Do It: the Use And Pitfalls Of Intracranial Vessel Walmentioning
confidence: 99%
“…Theoretically, the ideal VW imaging protocol would include images of all three image contrast weightings and a T1-weighted sequence after contrast agent administration to assess intracranial VW disease in the same fashion as has been done for years for their extracranial counterparts (46). However, no clear evidence yet exists on the clinical relevance of multicontrast MR imaging protocols for intracranial VW disease.…”
Section: How I Do It: the Use And Pitfalls Of Intracranial Vessel Walmentioning
confidence: 99%
“…MRI also can assess the presence of neovasculature in carotid artery plaques [82][83][84][85]. A recent study by Gaens et al [85] showed that dynamic contrast-enhanced MR of carotid atherosclerotic plaques can assess plaque neovasculature and that the Patlak model is well-suited for describing carotid plaque enhancement; the authors found that the K(trans) is an indicator of plaque microvasculature (validated by histology) and that the reproducibility of K(trans) was good.…”
Section: The Plaque Neovascularizationmentioning
confidence: 99%
“…9 This technique, which requires dedicated surface coils, has been used extensively for carotid atherosclerosis and, more recently, for carotid dissection. [10][11][12] Except for 1 case study, 13 there are no data in the literature that support a role for HR-MR imaging in the diagnosis of VAD.…”
mentioning
confidence: 99%